Electronic Metal-Support Interactions Between CuxO and ZnO for CuxO/ZnO Catalysts With Enhanced CO Oxidation Activity - Lyu, Shuai; Zhang, Yuhua; Li, Zhe; Liu, Xinyue; Tian, Zhenfang; Liu, Chengchao; Li, Jinlin; Wang, Li (Frontiers in Chemistry, 2022)
Metal-support interaction has been one of the main topics of research on supported catalysts all the time. However, many other factors including the particle size, shape and chemical composition can have significant influences on the catalytic performance when considering the role of metal-support interaction. Herein, we have designed a series of CuxO/ZnO catalysts as examples to quantitatively investigate how the metal-support interaction influences the catalytic performance. The electronic metal-support interactions between CuxO and ZnO were regulated successfully without altering the structure of CuxO/ZnO catalyst. Due to the lower work function of ZnO, electrons would transfer from ZnO to CuO, which is favorable for the formation of higher active Cu species. Combined experimental and theoretical calculations revealed that electron-rich interface result from interaction was favorable for the adsorption of oxygen and CO oxidation reaction. Such strategy represents a new direction to boost the catalytic activity of supported catalysts in various applications.